Global nutritional profiling for mutant and chemical mode-of-action analysis in filamentous fungi. - Tanzer,MM; Arst,HN; Skalchunes,AR; Coffin,M; Darveaux,BA; Heiniger,RW; Shuster,JR (Funct Integr Genomics, 2003)
We describe a method for gene function discovery and chemical mode-of-action analysis via nutrient utilization using a high throughput Nutritional Profiling platform suitable for filamentous microorganisms. We have optimized the growth conditions for each fungal species to produce reproducible optical density growth measurements in microtiter plates. We validated the Nutritional Profiling platform using a nitrogen source utilization assay to analyze 21 Aspergillus nidulans strains with mutations in the master nitrogen regulatory gene, areA. Analysis of these data accurately reproduced expected results and provided new data to demonstrate that this platform is suitable for fine level phenotyping of filamentous fungi. Next, we analyzed the differential responses of two fungal species to a glutamine synthetase inhibitor, illustrating chemical mode-of-action analysis. Finally, a comparative phenotypic study was performed to characterize carbon catabolite repression in four fungal species using a carbon source utilization assay. The results demonstrate differentiation between two Aspergillus species and two diverse plant pathogens and provide a wealth of new data on fungal nutrient utilization. Thus, these assays can be used for gene function and chemical mode-of-action analysis at the whole organism level as well as interspecies comparisons in a variety of filamentous fungi. Additionally, because uniform distribution of growth within wells is maintained, comparisons between yeast and filamentous forms of a single organism can be performed.